The importance of maintaining vitamin D levels for the immune system (Research, Society and Development, 2021)
Introduction: Vitamin D is one of the nutrients in which the close relationship between its organic status and the functioning of the Immune system has been established. Its need is met through the ingestion or supplementation of foods such as fatty fish such as salmon, tuna, sardines, irradiated mushrooms, among others, and its importance for the human body is indisputable. Objective: To describe the importance of vitamin D for the immune system, as well as its role in preventing autoimmune diseases. Methodology: To carry out this study, we opted for a research in the modality of integrative literature review. This method is appointed as a tool of great relevance in the field of health, as it provides the search, critical assessment and synthesis of evidence on an investigated topic. Results and Discussion: The nutritional aspects that surround a person are extremely important in the balance of the immune system, playing a fundamental role in maintaining the individual's health, including for patients with autoimmune diseases. Conclusion: It was evident through the development of this study that vitamin D plays an important role in the regulation of the immune system and, probably, in the prevention of immune-mediated diseases.